Workplace interventions to improve well-being and reduce burnout for nurses, physicians and allied healthcare professionals: a systematic review - Cohen, Catherine; Pignata, Silvia; Bezak, Eva; Tie, Mark; Childs, Jessie (BMJ open, 2023)
There is a growing need for interventions to improve well-being in healthcare workers, particularly since the onset of COVID-19.ObjectivesTo synthesise evidence since 2015 on the impact of interventions designed to address well-being and burnout in physicians, nurses and allied healthcare professionals.DesignSystematic literature review.Data sourcesMedline, Embase, Emcare, CINAHL, PsycInfo and Google Scholar were searched in May–October 2022.Eligibility criteria for selecting studiesStudies that primarily investigated burnout and/or well-being and reported quantifiable preintervention and postintervention outcomes using validated well-being measures were included.Data extraction and synthesisFull-text articles in English were independently screened and quality assessed by two researchers using the Medical Education Research Study Quality Instrument. Results were synthesised and presented in both quantitative and narrative formats. Meta-analysis was not possible due to variations in study designs and outcomes.ResultsA total of 1663 articles were screened for eligibility, with 33 meeting inclusion criterium. Thirty studies used individually focused interventions, while three were organisationally focused. Thirty-one studies used secondary level interventions (managed stress in individuals) and two were primary level (eliminated stress causes). Mindfulness-based practices were adopted in 20 studies; the remainder used meditation, yoga and acupuncture. Other interventions promoted a positive mindset (gratitude journaling, choirs, coaching) while organisational interventions centred on workload reduction, job crafting and peer networks. Effective outcomes were reported in 29 studies, with significant improvements in well-being, work engagement, quality of life and resilience, and reductions in burnout, perceived stress, anxiety and depression.ConclusionThe review found that interventions benefitted healthcare workers by increasing well-being, engagement and resilience, and reducing burnout. It is noted that the outcomes of numerous studies were impacted by design limitations that is, no control/waitlist control, and/or no post intervention follow-up. Suggestions are made for future research.